2016
DOI: 10.6017/ital.v35i4.9469
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Vendor-Created Database Tutorials for People with Disabilities

Abstract: Many video, screencast, webinar, or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In many of the cases in which there were no placement issues, there was also no fonted information on screen. YouTube's speech-to-text performed better than one might expect based on Oud (2016) and performed particularly well with speakers with relatively unaccented American English. It was relatively rare for captions to include background information.…”
Section: Adherence To Captioning Standardsmentioning
confidence: 67%
See 1 more Smart Citation
“…In many of the cases in which there were no placement issues, there was also no fonted information on screen. YouTube's speech-to-text performed better than one might expect based on Oud (2016) and performed particularly well with speakers with relatively unaccented American English. It was relatively rare for captions to include background information.…”
Section: Adherence To Captioning Standardsmentioning
confidence: 67%
“…While companies like YouTube have worked to improve their automated captions, researchers examining educational material found that automated captions were often, at best, difficult to use and called for content creators to take the time to edit You-Tube's auto-generated captions (Oud, 2016). This problem of poor quality autogenerated captions has led some in the disability advocacy community to refer to them as "craptions."…”
Section: Captioningmentioning
confidence: 99%
“…However, one of the most common themes that arises in regard to providing services to this unique population, is the idea of making library audiovisual materials accessible through the use of text alternatives such as transcripts or captions. Some authors have discussed the use of captions in the context of internally created library instructional materials (Clossen, 2014;Parton, 2015;Clossen and Proces, 2017), while others have emphasized the importance of transcripts or captions regarding library collections or purchased content such as DVDs and streaming video databases (Riley, 2009;Oud, 2016). When it comes to developing instructional materials such as videos and tutorials, libraries are increasingly realizing the importance of providing captions.…”
Section: Distance Library Services For Deaf and Hard Of Hearing Usersmentioning
confidence: 99%
“…The problem with automatically generated captions is their notorious inaccuracy, which can alter the meaning of content and decrease comprehension for individuals who rely solely on the text to learn material. (Parton, 2015;Oud, 2016;Clossen and Proces, 2017;Smith, Allman, and Crocker, 2017). For example, in another study, Parton (2015) found that for every minute of YouTube captions, there was an average of 7.7 phrases "that were unintelligible or altered the meaning of the message" (p. 12).…”
Section: Distance Library Services For Deaf and Hard Of Hearing Usersmentioning
confidence: 99%
“…Common accessibility problems include the lack of alternate descriptions, using visual cues to describe interactions in the user interface, fuzzy visuals, and audios. 10 Furthermore, the sightcentered nature of the digital library creates problems for blind users, such as the absence of meaningful descriptions for nontext content and instructions, along with information about the digital library's features due to missing textual or verbal instructions. 11 The traditional usage of a digital library makes a canned or routine utilization of its collections, which may be broadened by making computational ready collections.…”
Section: Introductionmentioning
confidence: 99%